Multicentre evaluation of targeted and systematic biopsies using magnetic resonance and ultrasound image-fusion guided transperineal prostate biopsy in patients with a previous negative biopsy - Hansen, Nienke Lynn; Kesch, Claudia; Radtke, Jan Philipp; Bonekamp, David; Schlemmer, Heinz-Peter; Wieczorek, Kathrin; Hohenfellner, Markus; Hadaschik, Boris (BJU international, 2017)
Objectives To evaluate the detection rates of targeted and systematic biopsies in magnetic resonance imaging (MRI) and ultrasound (US) image-fusion transperineal prostate biopsy for patients with previous benign transrectal biopsies in two high-volume centres. Patients and Methods A two centre prospective outcome study of 487 patients with previous benign biopsies that underwent transperineal MRI/US fusion-guided targeted and systematic saturation biopsy from 2012 to 2015. Multiparametric MRI (mpMRI) was reported according to Prostate Imaging Reporting and Data System (PI-RADS) Version 1. Detection of Gleason score 7-10 prostate cancer on biopsy was the primary outcome. Positive (PPV) and negative (NPV) predictive values including 95% confidence intervals (95% CIs) were calculated. Detection rates of targeted and systematic biopsies were compared using McNemar's test. Results The median (interquartile range) PSA level was 9.0 (6.7-13.4) ng/mL. PI-RADS 3-5 mpMRI lesions were reported in 343 (70%) patients and Gleason score 7-10 prostate cancer was detected in 149 (31%). The PPV (95% CI) for detecting Gleason score 7-10 prostate cancer was 0.20 (±0.07) for PI-RADS 3, 0.32 (±0.09) for PI-RADS 4, and 0.70 (±0.08) for PI-RADS 5. The NPV (95% CI) of PI-RADS 1-2 was 0.92 (±0.04) for Gleason score 7-10 and 0.99 (±0.02) for Gleason score ≥4 + 3 cancer. Systematic biopsies alone found 125/138 (91%) Gleason score 7-10 cancers. In patients with suspicious lesions (PI-RADS 4-5) on mpMRI, systematic biopsies would not have detected 12/113 significant prostate cancers (11%), while targeted biopsies alone would have failed to diagnose 10/113 (9%). In equivocal lesions (PI-RADS 3), targeted biopsy alone would not have diagnosed 14/25 (56%) of Gleason score 7-10 cancers, whereas systematic biopsies alone would have missed 1/25 (4%). Combination with PSA density improved the area under the curve of PI-RADS from 0.822 to 0.846. Conclusion In patients with high probability mpMRI lesions, the highest detection rates of Gleason score 7-10 cancer still required combined targeted and systematic MRI/US image-fusion; however, systematic biopsy alone may be sufficient in patients with equivocal lesions. Repeated prostate biopsies may not be needed at all for patients with a low PSA density and a negative mpMRI read by experienced radiologists.